The CSY-protecting group in the microwave-assisted synthesis of aggregation-prone peptides - Pham, Truc Lam; Zilke, Jennifer; Müller, Christine Charlotte; Thomas, Franziska (RSC chemical biology, 2022)
This report describes the application of cyanosulfurylide (CSY)-protected aspartatic acid building blocks in microwave-assisted synthesis of aggregation-prone protein domains. We present a synthesis of Fmoc-Asp(CSY)-OH on a multigram scale, as well as procedures for the microwave-assisted synthesis of CSY-protected peptides, and CSY cleavage in partially folded or aggregation-prone peptides.